Of carrots and sticks: The effect of workfare announcements on the job search behaviour and reservation wage of welfare recipients - Katrin Hohmeyer; Joachim Wolff (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The German workfare scheme `One-Euro-Jobs' that provides additional jobs of public interest for welfare recipients has a number of different goals. One the one hand, One-Euro-Jobs are intended to increase the participants' employment prospects in the medium term. On the other hand, they can be used to test welfare recipients' willingness to work. Using survey data from the Panel Study “Labour Market and Social Security” and propensity score matching methods, we study the effect of receiving a One-Euro-Job announcement on job search behaviour, reservation wage and labour market performance of welfare recipients. We find that receiving a One-Euro-Job announcement increases job search activities and decreases the reservation wage significantly, whereas no effects on the short-term employment probability can be found.
Keywords: J64; J68; I38; 330